Assessment of the anti-oxidative potential of Nepeta crispa Willd. (Lamiaceae) and its effects on oxidative stability of virgin sunflower oil under accelerated storage conditions - Mohamadreza Motaghed; Amir Nili-Ahmadabadi; Shirin Moradkhani (Institue of Medicinal Plants, ACECR, 2022)
Background: Nepeta crispa, is an annual plant native to certain regions of Hamadan province in Iran. Objective: This study aims to investigate the antioxidant potential of N. crispa. Methods: Hydro-distillated essential oil and methanol extract from aerial parts of N. crispa were obtained. They were subjected to several assays (DPPH, FRAP, TBARS, peroxide value and β-carotene-linoleic acid assay) in order to evaluate their antioxidant properties and their effect on prevention of oxidation in sunflower oil. Results: The extract consistently exhibited more activity than the essential oil in each and every one of the assays. The activity of the essential oil was not significant compared to positive controls or even the extract. The results from DPPH and FRAP assays correlated well with one another but those obtained from β-carotene-linoleic acid assay were to some extents inconsistent with the others. The results from TBARS and peroxide value assays revealed that certain concentrations of the extract effectively prevent the oxidation process in sunflower oil. Conclusion: Our data suggest that the methanol extract of N. crispa may be considered as novel bio-resource of natural antioxidants for using in pharmaceutical and food industries. Hopefully as the future research progress, new lights will be shed on characterization of components in the extract and the mechanisms through which they provide antioxidant activity.